Parerga to the Stadiasmus Patarensis (15): The Road Network around Kasaba Plain - Fatih Onur (Gephyra, 2015)
This article examines some missing parts concerning the Kasaba Plain and some road connections on Alacadağ, in respect to the Stadiasmus Patarensis (SP). The unknown destination of R 58 (from Myra) that is connected with the road network problems around Dereağzı, the absence of some important roads around Arneai and Dereağzı, and the blank section on top of Face C of the SP present some puzzling issues. One of two roads from Myra is Limyra (R 59), while the destination of other can unfortunately be restored insecurely due to erosion in the relevant part on the block. The propositions as to this destination are Dereağzı (Mastaura?) and Arneai. The author finds these propositions unlikely based upon the autonomy of the settlements and their geographical adaptability both in the field and on the SP, and proposes Trebendai, as an autonomous settlement near to Myra. Since the missing roads around the Kasaba Plain should fit in the blank section, the author discusses if the first road in the blank section could have been to Arneai (as was proposed by Şahin) or to Trebendai from Limyra, which is the last station in the road given from Arykanda (R 39) in the list on Face B that continues with the blank section on Face C. The author removes Dereağzı (Mastaura?) from the former propositions and establishes the roads in the blank section between Arneai, Myra, Limyra, Neisa, Kyaneai and Trebendai.